Vasor: Accurate prediction of variant effects for amino acid substitutions in multidrug resistance protein 3. Issue 11 (16th September 2022) - Behrendt, Annika; Golchin, Pegah; König, Filip; Mulnaes, Daniel; Stalke, Amelie; Dröge, Carola; Keitel, Verena; Gohlke, Holger
Abstract: The phosphatidylcholine floppase multidrug resistance protein 3 (MDR3) is an essential hepatobiliary transport protein. MDR3 dysfunction is associated with various liver diseases, ranging from severe progressive familial intrahepatic cholestasis to transient forms of intrahepatic cholestasis of pregnancy and familial gallstone disease. Single amino acid substitutions are often found as causative of dysfunction, but identifying the substitution effect in in vitro studies is time and cost intensive. We developed variant assessor of MDR3 (Vasor), a machine learning‐based model to classify novel MDR3 missense variants into the categories benign or pathogenic. Vasor was trained on the largest data set to date that is specific for benign and pathogenic variants of MDR3 and uses general predictors, namely Evolutionary Models of Variant Effects (EVE), EVmutation, PolyPhen‐2, I‐Mutant2.0, MUpro, MAESTRO, and PON‐P2 along with other variant properties, such as half‐sphere exposure and posttranslational modification site, as input. Vasor consistently outperformed the integrated general predictors and the external prediction tool MutPred2, leading to the current best prediction performance for MDR3 single‐site missense variants (on an external test set: F1‐score, 0.90; Matthew's correlation coefficient, 0.80). Furthermore, Vasor predictions cover the entire sequence space of MDR3. Vasor is accessible as a webserver at https://cpclab.uni‐duesseldorf.de/mdr3_predictor/ for users to rapidly obtain prediction results and a visualization of the substitution site within the MDR3 structure. The MDR3‐specific prediction tool Vasor can provide reliable predictions of single‐site amino acid substitutions, giving users a fast way to initially assess whether a variant is benign or pathogenic. Abstract : We developed Vasor (Variant assessor of MDR3), a machine learning‐based model to classify novel MDR3 missense variants into the categories of benign or pathogenic. Vasor was trained on the, to date, largest dataset specific for MDR3 of benign and pathogenic variants. Vasor consistently outperformed the integrated general predictors and the external prediction tool MutPred2.image